A Roadmap for Plant Genome Editing - Ricroch, Agnès; Eriksson, Dennis; Miladinović, Dragana; Sweet, Jeremy; Van Laere, Katrijn; Woźniak-Gientka, Ewa (Springer Nature, 2024)
This open access book is an update of genome editing techniques applied to a range of plants. We discuss the latest techniques and applications to cereals, roots and tubers, oilseed crops, fruit and forest trees, vegetables, legumes and algae including resistance to biotic and abiotic stresses, improved quality, drug production, yield and adaptation to climate change. The regulations in different countries worldwide, the patentibility and the perception by society of the applications of new genomic techniques are examined. This book is written by a multidisciplinary and multisectoral collective of high-profile scientists and other experts belonging to the COST Action network PlantEd, which is mainly European but with contributions from American, Australian, Canadian, Chinese, Indian, Iranian, Pakistani and Peruvian scientists. The book is aimed at a wide audience consisting of students, academics, private and public breeders, other actors in the food and bioeconomy value chains and policy and law makers. This is an open access book.